(untitled) (Filološke pripombe, 2019)
Taking into consideration Hugo Schuchardt’s viewpoint that language mixing is the question of the greatest importance of all the questions contemporary linguistics must tackle, the languages in contact issue imposes itself as the key one in the contemporary research. The subject of interest is the globalization process in linguistic context, as well as its influence on the Macedonian language, especially the Macedonian language system, followed it through several levels and examples, and giving a review of some of the existing research of the area. In terms of lexis, the discussion is about lexical borrowing as a new-denotat phenomenon, as well as about sociolinguistic borrowing. Regarding the word formation, the interest is on the suffix -ира, zero affixation found in the loan words and reactualisation of the Turkish suffix -џија/-чија. There is less influence in morphology, and in the field of syntax: noun+noun compounds, the language europeisation process and the English impersonal it, translated as тоа in the Macedonian impersonal sentences. Some idioms enter directly in the Macedonian language system through translation.